MR imaging evaluation for the assessment of pelvic organ prolapse: a newer technique - Dave, Anupama; Joshi, Ruchi; Goel, Vibhu; Dave, Atisha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: MRI is the newest technique used to evaluate patients with pelvic floor disorders. It allows relatively non-invasive, dynamic evaluation of all pelvic organs in multiple planes and can directly visualize the muscular and ligamentous pelvic floor support structures. Using MRI to evaluate pelvic floor disorders may be most helpful in patients with multicompartment findings or symptoms, posterior compartment abnormalities, severe prolapse, or recurrent pelvic floor symptoms after prior surgical repair. MRI is often able to reveal more extensive organ prolapse than physical examination alone. Methods: The present study was carried out in the Department of Radiodiagnosis and Obstetrics and Gynecology of Mahatma Gandhi Memorial Medical College and M.Y. Hospital, Indore, Madhya Pradesh from November 2014 to October 2015. A total of 43 patients who had symptoms of pelvic floor dysfunction like uterine prolapse, urinary or rectal dysfunction were evaluated by high resolution USG. Patients with low lying uterus on USG were subjected to MRI. Before MRI, these patients were assessed by a Gynecologist, and a clinical diagnosis in form of the organ/organs prolapsed and the grade of individual prolapse was assigned and tabled in the prefixed format. Results: Prolapse is more common in patients with greater than 50 years age (63% patients). MRI picked up more lesions compared to clinical examination, 90% as compared to 82.5% on clinical examination. MRI has good correlation with surgery in diagnosing prolapse. Concomitant prolapse of the Anterior and Middle compartment is the most common clinical entity diagnosed on 52.5% patients in our set up. MRI has poor sensitivity in identifying posterior compartment prolapse. There is good agreement between the clinical grading and MRI grading (81.8% correlation). Conclusions: T MRI offers a novel approach of simultaneous imaging of all compartments of the female pelvis at a single setting. With lesser intraobserver variation and better visualization of the pelvic anatomy MRI would help in accurate staging and hence better outcomes in patients in terms of symptom relief.